Conversational AI for companionship - Khan, Zakaria; Akash, Salauddin Md; Jamima, Afia Mobassira; Ishan, Isfar Hasan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.